Pelaksanaan Kegiatan Pascapenulisan melalui Bedah Sastra Pesantren Karya Santriwati MAS NIPI Ponpes Rasyidiyah Khalidiyah - Normuliati, Sri (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
The aim of this community service is to provide knowledge on writing pesantren literature and to assist in the final revision of pesantren works by the female students of MAS NIPI (Madrasah Aliyah Normal Islam Puteri) at Pondok Pesantren Rasyidiyah Khalidiyah. This community service was conducted in one meeting using lecture and discussion or Q&A methods. In the lecture method, the material on the basics of writing short stories is presented, along with an analysis of short stories written by the female students of MAS NIPI Ponpes Rasyidiyah Khalidiyah. Then, in the discussion or Q&A session, the focus is on the process of writing short stories and the works of the female students of MAS NIPI Ponpes Rasyidiyah Khalidiyah. The activity took place on Saturday, October 26, 2024, with 30 participants in attendance. The results indicate that the pesantren literature produced by the female students of MAS NIPI Ponpes Rasyidiyah Khalidiyah meets the narrative elements but still needs to pay attention to linguistic rules. During the activity, the female students were actively engaged. They asked questions about the writing challenges they faced and how to overcome them. The final outcome of this activity is the publication of an anthology/collection of pesantren literature created by the female students. The pesantren literature produced focuses on pesantren traditions, contains religious values, and portrays female figures as individuals with opportunities for education. It is hoped that this activity will foster the interest of female students in writing pesantren literature.